Pengembangan Model Mesin X-ray Menjadi Kamera Handphone Berteknologi Sinar X - Dony Efendi; Muhammad Aqshol Madinah; Muhammad Ashari; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2023)
This study aims to develop a model of an x-ray machine into a simpler form. This study used the Research and Development (R&D) research method with the Dick and Carey model. Prior to further development, the developer conducted a literature study through journals published by the Islamic University of Lamongan. The results of the journal state that the X-ray machine is a machine that functions as an inspection of passenger baggage which can be in the form of organic and non-organic materials, metal and non-metal as well as materials containing explosives without opening suitcases or bags, boxes or containers as material wrappers. using X-rays. Then in the development process it is carried out in a hierarchical order and an expert review is also carried out through material experts, instructional design experts, and media experts.